Investigation of pipe materials and thermal conductivity of soil on the performance of ground heat exchanger operating under Malaysia climate - Aizzuddin, A. M.; Taib, M. Y.; Azmi, W. H. (IOP Publishing, 2021)
In nature, renewable energy is inherently free and must be implemented. The use of air conditioning and refrigerants that affect global warming is a serious issue. In building applications, renewable energy from the geothermal source, namely ground heat exchanger (GHE), has great potential. The main concept of GHE is utilizing the ground as an infinite thermal reservoir for cooling and heating to the fluid medium. In the GHE system, the air is used as a fluid medium of work. Because of the temperature difference between the air and underground temperature, the air cools in summer and gets heated in winter. In this present work, a study has been conducted to investigate the effect of pipe materials and thermal conductivity of soil on the performance of the GHE. The study acknowledges that the pipe materials do not give a significant effect on the performance of the GHE. Therefore, the lower thermal conductivity of pipe materials with low cost can be used in GHE implementation. The study also revealed that the range of thermal conductivity of soil which gives good ground heat exchanger performance is between 1.5 to 5 W/m·K. Besides, the length of the pipe was reduced from 25 to 10 meters.